Business Strategy Formulation Based on SWOT Analysis: Case Study of PT Hatten Wine Bali - Farid Ardyansyah; I Nyoman Tri Sutaguna; Irwan Moridu; Pandu Adi Cakranegara; Dedik Wiryawan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study is to analyze business strategy formulation based on strengths, weaknesses, opportunities, and threats (SWOT) analysis, case study of PT Hatten Wine Bali. This type of research is a qualitative research with descriptive method. The type of data used is secondary data and data collection using observation. The analysis technique used is SWOT analysis. The results of this study indicate that PT Hatten Wine Bali already has more value than other competitors, which is supported from the production process to the quality of the final product which is so selective that the quality of the product becomes the main reference.